SCREENING OF MARINE ACTINOMYCETES FOR THEIR ANTIMICROBIAL AND ANTIFUNGAL ACTIVITIES IN EGYPT - WAFAA M. HAGGAG; RADWANEL-SEHEMY I.A (International Journal of Pharma and Bio Sciences, 2014)
The genus Streptomyces is represented in nature by the largest number of species and varieties among the family Actinomycetaceae. This study aims to isolate and characterize novel strains of Streptomyces with high antimicrobial and antifungal production capability. The morphological , biochemical and biological characteristics of marine actinomycetes isolated from the coast of the red sea of Seini , Egypt, are presented. A total of 50actinomycetes isolates were isolated by serial dilution plate technique, of these 20 isolates showed activity in primary screening against test pathogens used in this study.Antimicrobial activity of cultivation medium was determined using the diffusion - disc method. As test microorganisms Bacillus Subtilis, Bacillus cereus, Escherichia coli,Pseudomonasaeruginosa, Lactobacillus caseiand Candida albicans, are applied. The same isolates showed inhibitory effects against pathogenic fungi i.e. Alternariaalternata, A. solani, Colletotrichumgloeosporioides, Fusariumoxysporum, Aspergillusflavus andAspergillusniger. This may indicate the same compound was responsible for the antibacterial activity of the actinomycetes. Out of 20 isolates, 13 isolates exhibited both antibacterial and antifungal activity.Finally potent actinomycetalisolate were selected and it’s tested for enzymes production. The isolates were produced most important hydrolytic enzymes as chitinase and β-1, 3 glucanase , cellulose and protease. The culture filtrate of these strains were effective against Alternariaalternata, A. solani and Colletotrichumgloeosporioidesin tomato under greenhouse conditions.